Pengukuran Kepuasan Pelanggan Menggunakan Konsep Fuzzy Inference System - Yusran, Rio Rahmat (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2024)
Currently, the development of E-commerce in Indonesia has significantly increased, evidenced by the high volume of sales conducted both directly and indirectly. To enhance sales outcomes, producers must provide services that ensure customer satisfaction, thereby generating profits. Customer satisfaction needs careful attention to maintain competitiveness in the market. The criteria for improving customer satisfaction consist of four variables: 1. Product Quality, 2. Service Quality, 3. Product Price, and 4. Product Accessibility. The research issue identified by the researcher is the lack of understanding among sellers in addressing these criteria, resulting in inconsistent purchase intensity. The objective of this study is to assist sellers in enhancing satisfaction criteria to foster continuous customer purchases and sustain seller viability, ultimately boosting sales results. The method employed is the Sugeno method, involving four stages: fuzzification, inference engine, application and implication functions, and finally, defuzzification, using AND operators and MAX calculations. This study can serve as a decision-making system to improve customer satisfaction.